Revitalization Indonesian Language Learning in Higher Education: Evaluation Quality and Its Implications to Student Academic Competence - Moh. Zainudin (Kirana Publisher (KNPub), 2025)
Mastery of Indonesian is component essential in support competence communication students in the environment education high , good in context academic and professional . This research aim For evaluate effectiveness learning eye Indonesian language courses through approach studies case study focused on one study program at a university institutions college high . Approach methodology used covers interview in-depth , observation activity classroom learning , as well as review document learning . Findings studies indicates existence strength in practice teaching , especially in aspect interaction between lecturers and students who are taking place in a way constructive . However Thus , research this also identifies a number of challenges , especially in matter development material learning and its interrelationships with need current students . Therefore that , update more curriculum contextual as well as implementation method more learning interactive recommended use increase quality Indonesian language teaching . This study give contribution conceptual and practical in effort improvement quality Indonesian language learning at the elementary level education tall .